Tjiptojuwono, Eko PENGARUH TRAINING ADMINISTRASI PERKANTORAN TERHADAP EFEKTIVITAS KINERJA TATA USAHA SMA/SMK (Nsc Press, 2016)
This research was conducted to determine the effect of training with the office administration training to the performance effectiveness of administrative officers of general and vocational high school in Surabaya. This research was conducted by train administrative officers with the office administration for general and vocational high school in Surabaya. Researchers measuring the effectiveness and performance of the administration officers before and after training with the method of direct observation of the object of research, interviews, and questionnaires. The first phase, researchers conducted interviews with the principals and administrators in direct contact with the administrative services on general and vocational high school in Surabaya to find out information about the knowledge of office administration and performance of administration. The second phase, given training in office administration to administration officers. The third phase, researchers evaluate training results. Provision of office administration training to the administration officer on the general and vocational high school in Surabaya has an influence on enhancing the performance effectiveness of the administration officers.